Fixed time-off schedule: satisfaction of nursing assistants and technicians - Vanessa Monteiro Mantovani; Andréia Jandira Fonseca; Maria Henriqueta Luce Kruse; Amália de Fátima Lucena; Isabel Cristina Echer (Universidade Federal de Santa Maria, 2016)
Aim: to know the satisfaction of nursing technicians and assistants in relation to a fixed time-off schedule. Methods: qualitative research project, carried out in an inpatient unit of a university hospital, in Southern Brazil, between October and November 2013. Data collection occurred through interviews with 11 nursing technicians and assistants, who were individually interviewed. Data were analyzed using thematic content analysis as proposed by Bardin. Results: one category emerged from the analysis of the interviews: "Satisfaction with the fixed time-off schedule", and subcategories "Benefits for the personal lives of professionals" and "Benefits in the workplace for professionals" Final considerations: the fixed schedule promoted personal and professional satisfaction, as well as integration among the nursing staff, which may positively impact the work environment and the quality of care